Experiential Marketing Sebagai Determinan Dalam Meningkatkan Keterlibatan Pelanggan Dengan Loyalitas Merek (Studi Kasus pada Baso Aci Sambal Garut Tasikmalaya) - Ilman Ansori; Sumiarsih, Mia; Monika Sutarsa; Fidela Zahrah Azhari; Rizki Putri Annisa (JOURNAL INTELEKTUAL, 2025)
Introduction/Objective: This study aims to determine the influence between experiential marketing variables and customer engagement through brand loyalty, as well as to determine the factors that influence customer experience in restaurants, such as service, atmosphere, and the quality of products offered. Background of the Problem: In this modern era, companies are required to continue to innovate in increasing customer engagement with brands that prioritize direct customer experience with brands to create emotional attachment. Novelty: Analyzing popular Sundanese products in Tasikmalaya Regency by looking at customer experience. Research Method: Using a quantitative approach with a survey design. Data were collected by distributing questionnaires to restaurant customers who had visited more than once and path analysis techniques using the SmartPLS application program. Findings/Results: That experiential marketing has a positive and significant effect on customer engagement, both directly and indirectly through brand loyalty. Conclusion: Developing a richer customer experience strategy in strengthening promotional activities that involve customer emotions and senses.